From ionic to cellular variability in human atrial myocytes: an integrative computational and experimental study - Muszkiewicz, A; Liu, X; Bueno Orovio, A; Lawson, B; Burrage, K; Casadei, B; Rodriguez, B (American Physiological Society, 2017)
Variability refers to differences in physiological function between individuals, which may translate into different disease susceptibility and treatment efficacy. Experiments in human cardiomyocytes face wide variability and restricted tissue access; under these conditions computational models are a useful complementary tool. We conducted a computational and experimental investigation in cardiomyocytes isolated from samples of the right atrial appendage of patients undergoing cardiac surgery to evaluate the impact of variability in action potentials (APs) and sub-cellular ionic densities on calcium transient dynamics. Results show that: (1) Variability in APs and ionic densities is large, even within an apparently homogenous patient cohort, and translates into ±100% variation in ionic conductances; (2) Experimentally-calibrated populations of models with wide variations in ionic densities yield APs overlapping with those obtained experimentally, even if AP characteristics of the original generic model differed significantly from experimental AP’s; (3) Model calibration with AP recordings restricts the variability in ionic densities affecting upstroke and resting potential, but redundancy in repolarisation currents admits substantial variability in ionic densities; (4) Model populations constrained with experimental APs and ionic densities exhibit three calcium transient phenotypes, differing in intracellular Ca2+ handling and Na+/Ca2+ membrane extrusion. These findings advance our understanding of the impact of variability in human atrial electrophysiology.